Temporomandibular Joint Abscess by Streptococcus equi subsp. equi. (Research, Society and Development, 2022)
The present case report a equine, female, 6-year-old, crioulo breed, 400 kg, who was attended in theClinic and Surgery sector of Large Animals of the Federal University of Santa Catarina, presenting suppurative lesion near the temporomandibular region. In the clinic evaluation, moderate unilateral edema was observed in the region of the right temporomandibular joint (TMJ), and a drainage spot presenting a purulent exudate. The diagnosis was based on radiographic and ultrasound evaluation of the region, as well as laboratory findings of exudative sample culture. As a treatment based by a systemic and local antibiotic therapy was instituted, which was adjusted according to the laboratory results of bacterial culture and the clinical condition of the animal.  After 3 months after the beginning of the instituted treatment and the abscess drainage, the patient presented good clinical evolution. The aim is to report an abscess located in the TMJ caused by the agent Streptococcus equi subsp. equi with its probable origin in a previous strangles.